ChemInform Abstract: Synthesis of α‐Aryl‐diazophosphonates via Palladium‐Catalyzed Cross‐Coupling of Aryl Iodides with Diethyl Diazomethylphosphonate. Issue 18 (May 2015) - Kosobokov, Mikhail D.; Titanyuk, Igor D.; Beletskaya, Irina P.
Abstract In contrast to aryl iodides, aryl bromides and aryl chlorides are not applicable to the presented cross‐coupling reaction.